Thermal comfort and energy use in UK School buildings - Barbhuiya, S.; Barbhuiya, Salim; Nikraz, Hamid (International Journal of Structural and Civil Engineering Research, 2013)
This paper presents the results of an investigation on the effects of making changes to the design parameters of a generic school building. The design options are evaluated in order to study the performance of the building in terms of thermal comfort and energy use using two interventions under different climatic conditions (London and Stockholm). The building simulation is carried out using the IES software package and the thermal comfort metrics as defined in CIBSE Guide A. The summertime comfort and overheating have been evaluated on the basis of Building Bulletin - BB101. The findings demonstrate that combination of various design parameter scan help in reducing the effects of overheating in both the climates.